Study on the Tourism Sector in Mostaganem State: Diagnosis and Analysis - Ould said mohammed; Madouri noureddine; Chaa Abdelkader (Journal of North African Economies, 2025)
In the context of diversifying the national economy, the government considers the services sector in general and the tourism sector in particular to have significant growth potential that must be utilized. To this end, a principle has been developed to create a general strategic framework that aligns with regional differences to enhance tourism and make it a real lever for local development. This has prompted us to study the current state of the tourism sector in Mostaganem state through a comprehensive survey of all variables associated with this sector within the state.